Acrylamide‐induced autophagy‐lysosomal pathway dysfunction contributing to neurotoxicity through targeting transcription factor EB - Liuqing Yang; Li Dong; Lujia Zhang; Daotong Li; Yinghua Luo; Fang Chen (Food Frontiers, 2023)
Abstract Autophagy‐lysosomal pathway (ALP), a lysosome‐mediated self‐renewal process, is crucial for cell survival and death. Acrylamide (AA) is a neurotoxic compound produced during food thermal processing, and the mechanism underlying AA‐induced neurotoxicity remains elusive. In this study, we explored whether dysregulated ALP was involved in AA‐induced neurotoxicity and the underlying mechanism. We first evaluated the toxic effects of AA on the activation of apoptosis and NLRP3 pathway in human glioma U251 cells. We found that AA‐induced autophagy activation with the accumulation of an autophagy substrate P62, which implies the occurrence of autophagy‐lysosomal disorders. By using autophagy agonist PP242 and siRNA interfering ATG5, we demonstrated that ALP dysregulation contributed to AA‐induced apoptosis and NLRP3 inflammasome pathway activation. In addition, AA triggered ALP dysfunction by decreasing the expression of transcription factor EB (TFEB), and TFEB overexpression restored the lysosomal‐associated proteins and protected against AA‐induced apoptosis and inflammasome activation. Moreover, the autophagy agonist rapamycin restored AA‐induced ALP dysfunction by upregulating TFEB and prevented neurotoxicity. Overall, our study provides novel insights into the role of disrupted ALP in AA‐induced neurotoxicity and highlights that TFEB can be developed as a promising intervention target against AA‐induced neurotoxicity.